Heterogeneity in Price Elasticity of Medicine Demand in China: Moderate Effect From Economic Incentive and Quality Difference - Zhao, Mingyue; Nie, Peng; Wu, Jing (Frontiers in Pharmacology, 2021)
Previous studies show a wide range of drug price elasticity, but the price response to demand among various therapeutic drug categories and drug types (generic/originator) left unexplored yet in China, especially in a quality difference, unfair competition, and regulated market. Based on the bidding purchase policy, this study estimates the price elasticity of medicine demand using a dynamic panel model. Product-level data on anti-tumor, cardiovascular disease (CVD), and antimicrobial drugs was collected from the Tianjin Urban Employee Basic Medical Insurance database (2008–2010). The moderate effect of quality, profit incentive and illegal rebate is considered in the price elastic model. Our result suggest that the price elasticity for drug demand varied across drug categories, being least elastic for anti-tumor drugs and most elastic for CVD drugs (−0.192 for anti-tumor vs. −0.695 for antimicrobials vs. −1.100 for CVD drugs, P < 0.01). Moreover, the absolute value of price elasticity for generic is higher than that of the originator drugs in the antitumor and CVD therapeutic classes (interact: -0.716 for antitumor; -0.630 for CVD, P < 0.001). We believe that for these two kinds of generic drugs, quality difference plays a dominant role in the interaction between quality and illegal rebate. In the antimicrobial subgroup, the absolute value of price elasticity for generic medicine is lower than that of originator. We believe that due to the high level of unfair competition among enterprises, the role of illegal kickbacks is dominant, which reduces the price elasticity of demand for the generic antimicrobial drugs. Our research gives the final result of the game between quality and illegal rebate in different medicine market in China. Another main factors to impact the price elasticity is the disease type. Important implication of our study is that the price elasticity of drugs should be fully considered in order to prevent the shortage of drugs caused by the new purchasing policy. Second, the reform of physicians’ compensation system needs to be improved to promote rational drug use and generic drug substitution in China.